Сучасні підходи до проектування рецептур комбінованих багатокомпонентних м’ясних продуктів для військовослужбовців - Стеценко, Наталія Олександрівна; Сімахіна, Галина Олександрівна; Гойко, Ірина Юріївна (My University, 2015)
У статті представлені медико-біологічні рекомендації, які покладені в основу комп’ютерного моделювання рецептури печінкового паштету функціонального призначення для військовослужбовців Збройних Сил України. Наведено результати визначення показників біологічної ефективності розробленого продукту. The article represents the medical and biological recommendations that were used to plan the wide array of new foodstuffs for military personnel, based on the methods of computer modeling. The object of researches was meat pß^ enriched with plant raw materials. Upon using the method of gas chromatography, we have affirmed that the content of ю-6 fatty acids in a pß^ grew almost twofold comparatively to the initial amount, and the content of ю-3 acids grew fivefold, due to input of selected seed cultures (mustard, pumpkin, and sunflower seeds) into the recipe of the product. Generally, interaction between separate groups of fatty acid (FA) resulted in a correlation of Saturated FA : Mono-Non-Saturated FA : Poly-Non-Saturated FA as 3.4 : 5.3 : 1 (with a norm of 3 : 6 : 1). The level of absorption of proteins from the new-produced pß^ has increased on 8 per cent that is an evidence of higher nutritional and biological value of the products, which is a marker of their adequacy to the needs of warriors.
Keywords: кафедра технології оздоровчих продуктів; паштет; військовослужбовці; функціональні харчові продукти; моделювання; рецептура; pate; military personnel; functional foodstuffs; recipes; modeling